MEDIATION OF CSR AND PROFITABILITY ON THE INFLUENCES OF GCG MECHANISMS TO THE FIRM VALUE - Muhamad Umar Mai (Jurnal Keuangan dan Perbankan, 2017)
The purpose of this research was to determine the causal relationship among GCG mechanism, financial performance, CSR and firm’s value. The model of the research was constructed by using financial performance and CSR as intervening variables on the effect ofGCG mechanism to firm’s value. This research was accomplished on companies listed in Jakarta Islamic Index (JII) in Indonesia Stock Exchange for the period of 2007-2013. The result showed that GCG mechanism tended to reject every CSR financing. CSR was positively affected by Return on Investment (ROI). GCG mechanism represented by institutional ownership (INWN) had a positive effect on ROI. ROI had a positive effect to return on equity (ROE), and ROE had a positive effect on the firm’s value. This study proved that ROI was mediating significantly the effect of INWN to CSR, and ROE was mediating significantly the effect of ROI to firm’s value.